2014
DOI: 10.5194/nhess-14-1325-2014
|View full text |Cite
|
Sign up to set email alerts
|

Heavy rainfall episodes over Liguria in autumn 2011: numerical forecasting experiments

Abstract: Abstract. The Liguria coastal region in Italy was affected by two heavy rainfall episodes and subsequent severe flooding that occurred at the end of October and the beginning of November 2011. In both cases, the very large accumulated precipitation maxima were associated with intense and quasi-stationary convective systems that developed near the coast, both related to orographic lift and similar low-level mesoscale flow patterns over the Ligurian Sea, giving rise to pronounced convergence lines.This study aim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 33 publications
2
109
0
Order By: Relevance
“…On the other hand, from Table 3 (top), we can state that the model is able to capture the characteristics of a heavy rainfall event in the area of interest. In particular the maximum value achieved by the model in the whole area of interest (218 mm (24 h) −1 ) is similar to that obtained by Buzzi et al (2014), who analysed the same rainfall event with the ISAC convection-permitting MOLOCH model (Buzzi et al, 2004). In their paper, the authors found a maximum rainfall amount of 286 mm (24 h) −1 .…”
Section: Reliability Of Nwp Datasupporting
confidence: 82%
See 3 more Smart Citations
“…On the other hand, from Table 3 (top), we can state that the model is able to capture the characteristics of a heavy rainfall event in the area of interest. In particular the maximum value achieved by the model in the whole area of interest (218 mm (24 h) −1 ) is similar to that obtained by Buzzi et al (2014), who analysed the same rainfall event with the ISAC convection-permitting MOLOCH model (Buzzi et al, 2004). In their paper, the authors found a maximum rainfall amount of 286 mm (24 h) −1 .…”
Section: Reliability Of Nwp Datasupporting
confidence: 82%
“…4a and b. The general underestimation of NWP model forecast in predicting precipitation maxima during intense precipitation events is a well known issue and was recently addressed for this specific rainfall event by Buzzi et al (2014). On the other hand, from Table 3 (top), we can state that the model is able to capture the characteristics of a heavy rainfall event in the area of interest.…”
Section: Reliability Of Nwp Datamentioning
confidence: 87%
See 2 more Smart Citations
“…Due to self-regenerating storm cells or to persistent cyclonic Tyrrhenian circulation (Crosta 1998;Cevasco et al 2009), extreme precipitation can occur, between late summer and mid-autumn, along the coast of eastern Liguria (van Delden 2001;Silvestro et al 2012Silvestro et al , 2015Rebora et al 2013;Buzzi et al 2014;Cevasco et al 2015;Cassola et al 2016). Usually these rainstorms have short duration (<24 h), but rainfall intensities can reach or exceed values of 100 mm h ¡1 .…”
Section: General Features Of the Study Areamentioning
confidence: 99%